Exploring the Link Between Health Facilities and Dental Personnel Availability with Dental Service Utilization in South Buton District, Southeast Sulawesi Province - Marianti, Rita Dewi; Saafi, La Ode; Nurlila, Ratna Umi (Magister Kesehatan Universitas Mandala Waluya, 2024)
Introduction: Based on the data on visits and dental health service in the Public Health Centers over the past three years, a decrease in the number of visits has been observed. In 2019, there were 2,492 visits; in 2020 the number decreased to 1,040 visits; and in 2021, there was a further decline to 950 visits. The purpose of this study was to analyze the factors associated with the utilization of oral and dental health services in South Buton Regency. Method: This research was a quantitative study using a Cross-Sectional Study approach. The population in this study consisted of 1.805 visits, and the sample included a portion of the total visits by oral and dental patients at the public health centers in South Buton Regency, with 95 samples selected from 9 public health centers. Result: The research result indicate that the knowledge variable has a phi value of 0,391, access has a phi value of 0.359, facility availability for health services has a phi value of 0.290, and the availability of oral and dental health personnel has a phi value of 0.339. This indicates that all mentioned variables are weakly associated, except for the knowledge variable which has a moderate association with a utilization of oral and dental health services in South Buton Regency. Conclusion: The research results show that the variable availability of health service facilities has a phi value of 0.290 and the availability of dental and oral health workers has a phi value of 0.339.